Dietary patterns of adults in Italy: Results from the third Italian National Food Consumption Survey, INRAN-SCAI - Nicolò Scarsi; Roberta Pastorino; Cosimo Savoia; Gian Marco Raspolini; Angelo Maria Pezzullo; Stefania Boccia (PLoS ONE, 2025)
Diet is among the most significant modifiable risk factors for reducing the global burden of chronic diseases. This study aims to investigate the dietary patterns of adults in a large representative sample of the Italian population and to analyze these patterns according to sociodemographic characteristics. Adult participants of the third Italian National Food Consumption Survey were included. A total of 878 food items were classified into 24 pre-defined food groups using the FoodEx2 classification system. Dietary patterns were identified through principal component analysis, and Z-scores were calculated to assess adherence to these patterns. Associations between sociodemographic characteristics, energy intake, and dietary adherence scores were investigated using linear regression models. Based on data from 2,831 subjects (median age 47, IQR 35–60), five principal components (PCs) were retained, explaining 35.63% of the overall variance. PC1 was indicative of a high-fat diet, PC2 suggested a western eating behavior, PC3 represented a health-conscious lifestyle, PC4 can be characterized as an Italian traditional diet, and PC5 represented an unhealthy dietary pattern. According to Z-scores, 42.4% of our study cohort showed high adherence to at least one of the dietary patterns. Less healthy dietary patterns were more prevalent among males and individuals from northern Italian regions. Our results indicate a significant regional variation in terms of dietary pattern, mirroring the general trends of Italian eating habits of the last decades, characterized by a higher tendency towards a more westernized lifestyle. These findings underscore the importance of considering region-specific characteristics when designing future public health interventions and establishing, or updating, national dietary guidelines.